Impact of futsal and swimming participation on bone health in young athletes - Seabra, A.; Fernandes, R. J.; Marques, E.; Moura, M.; Ubago-Guisado, E.; Hernando, E.; Gallardo, L. (Journal of Human Kinetics, 2017)
Physical activity plays a crucial role in bone mass acquisition during childhood and adolescence, with weightbearing and high-impact sport activities being more beneficial. This study sought to evaluate the impact of different sports activities on bone mineral density and content in male Portuguese athletes. Seventy adolescent boys (aged 12-15 years) including 28 futsal players (FG), 20 swimmers (SG) and 22 non-athletic adolescents used as control subjects (CG), participated in the current study. Areal bone mineral density (aBMD) and areal bone mineral content (aBMC) were measured by dual energy x-ray absorptiometry (DEXA). Futsal players had significantly higher aBMD (lumbar spine - FG: 0.95 ± 0.18, SG: 0.80 ± 0.13, CG: 0.79 ± 0.13 g/cm2, p = 0.001; pelvis - FG: 1.17 ± 0.21, SG: 0.91 ± 0.12, CG: 0.98 ± 0.10 g/cm2, p < 0.001; lower limbs - FG: 1.21 ± 0.19, SG: 0.97 ± 0.10, CG: 0.99 ± 0.09 g/cm2, p < 0.001) and aBMC (lumbar spine - FG: 51.07 ± 16.53, SG: 40.19 ± 12.47, CG: 40.50 ± 10.53 g, p = 0.013; pelvis - FG: 299.5 ± 110.61, SG: 170.02 ± 55.82, CG: 183.11 ± 46.78 g, p < 0.001; lower limbs - FG: 427.21 ± 117.11, SG: 300.13 ± 76.42, CG: 312.26 ± 61.86 g/cm2, p < 0.001) than swimmers and control subjects. Data suggest that futsal, as a weightbearing and high or odd-impact sport, may improve bone mass during childhood and adolescence.